Does Neurotechnology Produce a Better Brain? - Bhattacharyya, Rajan; Coffman, Brian A.; Choe, Jaehoon; Phillips, Matthew E. (Computer (00189162), 2017)
Neurotechnologies in clinical applications can image the brain noninvasively, but they typically require surgical insertion to stimulate it. Although an increasingly popular alternative is to use noninvasive stimulation to enhance nervous system functions, questions about its effectiveness and ethical use remain unanswered.